2023
DOI: 10.1186/s12610-023-00213-y
|View full text |Cite
|
Sign up to set email alerts
|

Which inflammatory marker, between systemic immune-inflammation index and neutrophil to eosinophil ratio, is associated with Peyronie’s disease and are there any implications for a better understanding of its mechanisms?

Felice Crocetto,
Ciro Imbimbo,
Biagio Barone
et al.

Abstract: Background Peyronie’s disease affects up to 9% of men and is often accompanied by pain and/or erectile dysfunction. It is characterized by an inflammatory process that is the grassroots of the subsequent fibrosis stage. There is an unmet need to evaluate its onset and progression. Among the newly proposed biomarkers of inflammation, authors developed a novel systemic immune-inflammation index (SII) based on lymphocyte, neutrophil, and platelet counts. Similarly, a recent study reported that a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“… 14 In other male diseases, SII has been found to be associated with Peyronie's disease in men. 23 Our study found an increased risk of ED in participants with SII > 485.530. Taking together the findings of above studies, our findings were reasonable.…”
Section: Discussionsupporting
confidence: 44%
“… 14 In other male diseases, SII has been found to be associated with Peyronie's disease in men. 23 Our study found an increased risk of ED in participants with SII > 485.530. Taking together the findings of above studies, our findings were reasonable.…”
Section: Discussionsupporting
confidence: 44%